Mind the gap: Theories in Islamic accounting and finance, Islamic economics and business management studies - Murniati Mukhlisin; Nurizal Ismail; Reza Jamilah Fikri (ISRA International Journal of Islamic Finance, 2022)
Purpose - This study aims to analyse whether theories and views of classical Islamic scholars are widely adopted as references in Islamic accounting and finance (IAF), Islamic economics (IE) and Islamic business management (IBM) research studies as part of their contribution to solving current economic and financial problems. Design/methodology/approach - The research adopts a qualitative meta-analysis methodology using NVivo 12 with selected data from 474 international journal articles published between 1981 and 2021. The study considers 172 IAF articles, 111 IE articles and 191 IBM articles. Findings - The results of the study show that the use of theories and views of classical Islamic scholars is not widespread among the examined research papers. The findings show that 90% of researchers tend to acquire modern economics, management, psychological and sociological theories instead of classical theories. Both modern and classical theories have been discussed in the studied articles namely agency theory, stakeholders' theory, ḥisbah (accountability), maqāṣid al-Sharīʿah (objectives of Islamic law) and waʿd (unilateral promise). The gaps prevail not only in the taxonomy of terms but also in the choice of paradigm references. It is found that 66% of the 474 journal articles adopt a positivist paradigm, followed by interpretivism (19%), post-structuralism (9%) and critical orientation (6%). Research limitations/implications - This paper considers only ABS ranking journal articles. Future research may consider other journal articles from different ranking groups such as Scopus or Thomson & Reuters. Practical implications - The paper sheds light on how Islamic educational institutions can develop strategies for the Integration of Knowledge (IOK) in their curriculum. Social implications - This paper helps to shape the Muslims' way of thinking within an Islamic worldview which will lead to an Islamic way of expressing knowledge, skill and behaviour. Originality/value - This paper contributes to the model of IOK that has been deliberated among Islamic universities, especially those that develop IAF, IE and IBM studies.
Keywords: 330; Classical theories; Integration of knowledge; Islamic accounting and finance; Islamic business management; Islamic economics; Modern theories